2021
DOI: 10.1038/s12276-021-00617-8
|View full text |Cite
|
Sign up to set email alerts
|

Slimy partners: the mucus barrier and gut microbiome in ulcerative colitis

Abstract: Ulcerative colitis (UC) is a chronic recurrent intestinal inflammatory disease characterized by high incidence and young onset age. Recently, there have been some interesting findings in the pathogenesis of UC. The mucus barrier, which is composed of a mucin complex rich in O-glycosylation, not only provides nutrients and habitat for intestinal microbes but also orchestrates the taming of germs. In turn, the gut microbiota modulates the production and secretion of mucins and stratification of the mucus layers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(92 citation statements)
references
References 142 publications
1
91
0
Order By: Relevance
“…Considering one of the hallmarks of PPE lesions is the loss of goblet cells and the protective intestinal mucin layer (1,37), it is likely that bacteria other than L. intracellularis could contribute to the development of lesions as they would have increased access to the epithelium. Additionally, mucin is known to harbor antimicrobial peptides, which, if altered during infection, could also contribute to dysbiosis (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Considering one of the hallmarks of PPE lesions is the loss of goblet cells and the protective intestinal mucin layer (1,37), it is likely that bacteria other than L. intracellularis could contribute to the development of lesions as they would have increased access to the epithelium. Additionally, mucin is known to harbor antimicrobial peptides, which, if altered during infection, could also contribute to dysbiosis (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…β-defensin expression is known to be regulated by MUC2, a major component of the mucus layer in the gut which serves as an additional barrier between gut microbes and epithelial cells [29]. The mucus layer is also composed of a loose outer layer colonized by the gut microbiota and a firmer inner layer which serves as a diffusion barrier, separating the microbiota from epithelial cells [80]. The study by Gao et al [29] showed that 4 weeks of CRS was sufficient to decrease colonic MUC2 expression and goblet cell numbers.…”
Section: Intestinal Barrier Integrity Pathwaysmentioning
confidence: 99%
“…We found that Axin1 ΔIEC mice are protected from DSS-induced inflammation but have a weakened mucus barrier. It’s been shown that a depleted mucus barrier results in susceptibility to DSS-induced colitis [48, 49, 50]. However, increased Muc2 and Akkermansia muciniphilia have been shown to protect against DSS-colitis [30, 50], which collectively may allow the Axin1 ΔIEC mice to have increased colitis-protection compared to controls.…”
Section: Discussionmentioning
confidence: 99%